Perceived Effectiveness of Anambra State Government in Ensuring Sustainable Use of Rivers and Marine Resources - Ogbaka, L. C.; Ewelum, J. N.; Chieke, J. C.; Eme, U. U. (Journal of Research in Adult and Continuing Education, 2024)
The study determined the perceived effectiveness of the Anambra State Government in ensuring sustainable use of rivers and marine resources. One research question was formulated to guide the study and one null hypothesis was tested at 0.05 level of significance. The study used a descriptive survey research design. The population of the study was made up of 317 stakeholders in the area of environmental sustainability in Anambra State. No sampling was done because the population was manageable. The instrument used for data collection was a questionnaire. The reliability coefficient of the instrument which was 0.79 was determined using Cronbach’s alpha. The instrument was validated by three experts from the Departments of Educational Foundations, Science Education and Adult and Continuing Education in Nnamdi Azikiwe University, Awka. The instrument was distributed and collected by the researcher through the assistance of three research assistants. Only 302 copies of the questionnaire were completed and returned. The data collected were analysed using mean and analysis of variance (ANOVA). Post hoc analysis was conducted on the null hypothesis using bonferroni test for multiple comparisons. The finding of the study showed that the Anambra State Government was ineffective in ensuring sustainable use of river and marine resources. The study equally revealed that the staff of the Ministry of Environment, Presidents General/Caretaker Chairmen and staff of the Non-Governmental Organizations differed significantly in their mean ratings on the effectiveness of the Anambra State Government in ensuring sustainable use of rivers and marine resources. Based on the findings, it was concluded and recommended, among others, that the Anambra State Environmental Protection Agency and other environmental friendly agencies should extend their functions to the rural areas.